Investigating adsorption isotherms and kinetics, and ecotoxicity of activated carbon from carbon-fiber reinforced polymer (CFRP) - Nik Ahmad Shafrizal, Nik Misha Adrina; Nasaruddin, Ricca Rahman; Mansor, Mariatul Fadzillah; Abd Halim, Nor Farah Huda (IIUM Press, 2025)
This study presents the synthesis of activated carbon (AC) from carbon fiber reinforced polymer (CFRP) waste as a sustainable adsorbent for wastewater treatment. Characterization by FTIR, SEM, and XRD confirmed the development of functional groups, a porous morphology, and a predominantly amorphous carbon structure in AC, with minor graphitic domains in CFRP. Adsorption tests using the methylene blue (MB) dye showed good performance, with the Langmuir isotherm resulting in the best-fitted model (adjusted R² = 0.88), indicating monolayer adsorption and pseudo-first-order kinetics (adjusted R² = 0.96). Thus, confirming concentration-dependent adsorption of MB by AC, produced from CFRP. Ecotoxicity evaluation using brine shrimp assay revealed an LC50 of 33.11 mg (or 3311 mg/L), suggesting moderate toxicity. These findings demonstrate that AC derived from CFRP exhibits strong adsorption efficiency with acceptable ecological risk, providing a viable pathway to convert CFRP waste into valuable materials for environmental remediation